Inconsistency between Human Observation and Deep Learning Models: Assessing Validity of Postmortem Computed Tomography Diagnosis of Drowning - Zeng, Yuwen; Zhang, Xiaoyong; Wang, Jiaoyang; Usui, Akihito; Ichiji, Kei; Bukovsky, Ivo; Chou, Shuoyan; Funayama, Masato; Homma, Noriyasu (Journal of imaging informatics in medicine, 2024)
Drowning diagnosis is a complicated process in the autopsy, even with the assistance of autopsy imaging and the on-site information from where the body was found. Previous studies have developed well-performed deep learning (DL) models for drowning diagnosis. However, the validity of the DL models was not assessed, raising doubts about whether the learned features accurately represented the medical findings observed by human experts. In this paper, we assessed the medical validity of DL models that had achieved high classification performance for drowning diagnosis. This retrospective study included autopsy cases aged 8-91 years who underwent postmortem computed tomography between 2012 and 2021 (153 drowning and 160 non-drowning cases). We first trained three deep learning models from a previous work and generated saliency maps that highlight important features in the input. To assess the validity of models, pixel-level annotations were created by four radiological technologists and further quantitatively compared with the saliency maps. All the three models demonstrated high classification performance with areas under the receiver operating characteristic curves of 0.94, 0.97, and 0.98, respectively. On the other hand, the assessment results revealed unexpected inconsistency between annotations and models' saliency maps. In fact, each model had, respectively, around 30%, 40%, and 80% of irrelevant areas in the saliency maps, suggesting the predictions of the DL models might be unreliable. The result alerts us in the careful assessment of DL tools, even those with high classification performance.
Keywords: posmrtné zobrazování; lidé; mladiství; Adult; Middle Aged; Postmortem computed tomography; ROC křivka; počítačová rentgenová tomografie; Autopsy; dítě; Female; Validity assessment; deep learning; retrospektivní studie; Adolescent; Humans; pitva; Deep Learning; utonutí; lidé středního věku; Postmortem Imaging; mužské pohlaví; mladý dospělý; ROC Curve; Computer-aided diagnosis; ženské pohlaví; Young Adult; Aged, 80 and over; Tomography, X-Ray Computed; Deep learning; senioři nad 80 let; Male; Aged; Reproducibility of Results; reprodukovatelnost výsledků; Retrospective Studies; Child; dospělí; Drowning; senioři